Sistem Informasi Perpustakaan Pada SMKN 1 Ende Berbasis Website - Gebo, Alexander; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
SMKN 1 Ende has a library as one of the facilities provided by the school to support student learning activities. The existence of a library is very important in increasing knowledge for students in schools. However, based on the results of an interview conducted with one of the librarians of SMKN 1 Ende, currently school library data management is still using manual methods such as recording visitor member data, book data, borrowing data and returning books in the ledger. As a result, it is inefficient and has a very big risk of mistakenly recording data on borrowing and returning books and other problems that often occur, namely when searching for data on borrowing and returning books where librarians have to reopen existing files so that it takes time. long enough. To overcome the existing problems, it is necessary to make a school library information system that will be tailored to the needs of the library. Based on the description of the problems in the library of SMKN 1 Ende, the theme that will be discussed by the researcher is "Library Information System at SMKN 1 Ende is Website Based". With this system, it can help the data management process by library officers in carrying out their duties such as collecting data on library visitor members, data collection of books, data collection of borrowing transactions and returning books so that officers complete their duties quickly.